Impacts of extrinsic factors on early aging: A theoretical reflection (Research, Society and Development, 2021)
Objective: Describe the impacts of extrinsic factors on premature aging, from a theoretical reflection. Methodology: This is a reflective theoretical essay, through a non-systematic bibliographic review on the theme “extrinsic factors and premature aging”, and also through the authors perception of the theme. As a search strategy, eletronic databases and virtual libraries were defined, respectively Science Direct, Scielo and Google Scholar, using the descriptors standardized by the Health Sciences Descriptors (Decs): aging; skin aging; free radicals; smoking; premature senility, and their English counterparts. The survey was limited to articles published in Portuguese, English and Spanish, published in the period from 2010 to 2020, available in full and whose results covered the theme of this research. Results: The literature analysis was arranged in two sub-themes: “Cutaneous Aging” and “ Extrinsic Aging”. Final Considerations: When analyzing the topics covered, it is possible to verify how much extrinsic factors incluence premature aging and that to reduce this influence, people should choose a healthier life.